KONSTRUKSI SOSIAL KAWIN KONTRAK DI DESA TUGU UTARA DAN TUGU SELATAN KECAMATAN CISARUA KABUPATEN BOGOR - Rizki, Andini Putri; Zuryani, Nazrina; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 1 No 1 (2019), 2019)
ABSTRACT The background of this research is the phenomenon of contract marriage in the North and South Tugu villages, Cisarua District, Bogor Regency. Marriage contract is limited by the period according to the agreement of both parties which then ends automatically without divorce processes. Lack of means of economy and education for women in their productive age are the main reason for the practice of contract marriage in those villages. This study aims to analyse social construction of contract marriages in North and South Tugu Villages, and focuses on the meaning of women as the subject of contract marriage to their marital activity. This study uses qualitative methods by emphasizing the depth of data through analysis of social construction theory by Peter L. Berger and Thomas Luckman.   Keywords : Contract Marriage, Social Construction, North and South Tugu Villages